1995
DOI: 10.1039/ft9959103851
|View full text |Cite
|
Sign up to set email alerts
|

Steric solvent effect on small and large cations: calorimetric study of halogeno and thiocyanato complexes of beryllium(II) and cadmium(II) in N,N-dimethylacetamide

Abstract: Solution equilibria of beryllium(ll) and cadmium(ii) complexes with halide and thiocyanate ions are studied in N,N-dimethylacetamide (DMA) by calorimetry. Mononuclear Be" complexes, [BeX]' and [BeX,] (X = CI, SCN), and Cd" complexes, [CdX]', [CdX,], [CdXJ-and [CdX,]' -(X = CI, Br, I, SCN), are found, and their formation constants, enthalpies and entropies are determined. The Be" systems are also studied in N,N-dimethylformamide (DMF). Each of t h e Be" complexes has very similar thermodynamic quantities in DMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, the halogeno complexation behavior of a metal ion in DMA is quite different from that in DMF. [53][54][55][56][57][58][59][60][61][62] This is due to the solvation steric effect. To elucidate the solvation steric effect on metal-ion complexation, a knowledge of the structure of both the metal ion and its complex is indispensable.…”
Section: Discussionmentioning
confidence: 99%
“…However, the halogeno complexation behavior of a metal ion in DMA is quite different from that in DMF. [53][54][55][56][57][58][59][60][61][62] This is due to the solvation steric effect. To elucidate the solvation steric effect on metal-ion complexation, a knowledge of the structure of both the metal ion and its complex is indispensable.…”
Section: Discussionmentioning
confidence: 99%
“…N , N -Dimethylformamide (DMF) is a widely used organic, aprotic solvent. It has a high liquid range of −60 to +150 °C, is miscible with most protic and aprotic organic solvents, and dissolves rather nonpolar organic compounds as well as inorganic salts, which makes it a versatile solvent. , It should therefore be an excellent choice for the coordination chemistry of beryllium because DMF is capable of dissolving BeSO 4 ·4H 2 O, Be­(ClO 4 ) 2 ·4H 2 O and Be­(acac) 2 (acac = acetylacetone) . Nevertheless, little has been reported on beryllium chemistry in DMF, which is not surprising considering the fact that beryllium is the least investigated nonradioactive element .…”
Section: Introductionmentioning
confidence: 99%
“…The few studies on this topic refer to formation of the [Be­(DMF) 4 ] 2+ cation , or the equilibrium between DMF, competing solvents (L), and anions (X = SCN – , Cl – , ClO 4 – , SO 4 2– ). As a result, compounds [Be­(DMF) n (L) 4– n ] 2+ , and [Be­(DMF) n (X) 4– n ] (2– n )– were postulated. , However, these species were only predicted through titration and electrochemical measurements. Solely [Be­(DMF) 4 ]­(ClO 4 ) 2 was additionally characterized by elemental analysis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] Indeed, it has been found that the metal-ion complexation with simple halide and pseudohalide ions is generally enhanced in N,N-dimethylacetamide (DMA) over N,N-dimethylformamide (DMF), despite physicochemical properties of the solvents being similar. [11][12][13][14][15][16][17][18][19][20][21][22] Also, the complexation is significantly enhanced in hexamethylphosphoric triamide (HMPA) over DMF, and the solvation number of a metal ion decreases in HMPA relative to DMF, indicating a strong solVation steric effect operates in HMPA. [23][24][25][26][27] Solvation steric effect also modifies an aspect of preferential solvation (sterically controlled preferential solVation) of a metal ion in solvent mixtures.…”
Section: Introductionmentioning
confidence: 99%